Analysis of the Effect Rotation Speed Control on Three Phase Induction Motor Using VFD Powtech - Tri Safrizal; Adi Sastra P. Tarigan; Siti Annisah (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Technological advances in electric motor control systems have encouraged the adoption of more efficient and adaptive control devices. One of the commonly used devices is the Variable Frequency Drive (VFD), which plays a role in regulating the speed and torque of a three-phase induction motor. This study aims to analyze the effect of a three-phase induction motor rotational speed control system using a Powtech brand VFD. The main focus of this study is to evaluate motor performance in terms of rotational speed, torque, energy efficiency, and system response to frequency variations provided by the VFD. The research method used is an experimental approach, where a three-phase induction motor is connected to a Powtech VFD and tested under various load conditions and operating speeds. The test results show that the use of a Powtech VFD is able to provide more accurate speed and torque control, and contributes to increasing the efficiency of induction motor operation. In addition, smoother and more responsive rotation control can be achieved through flexible frequency adjustment, resulting in reduced power consumption and increased overall system performance. This study contributes to the development of VFD technology in three-phase induction motor drive systems, especially in efforts to improve energy efficiency in industrial applications.